Analysis of the human development index to the development of the province of west Sulawesi. Issue 1 (November 2021) - Ansyar, M. H.; Padjung, R.; Salam, M.
Abstract: Development success is measured by several parameters, one of which is the human development index. Humans have a role as a factor of production which is very important in the development of the region. This study aims to analyze which components make the human development index in the province of West Sulawesi low, and how the government's strategies and priorities in improving HDI to support regional development and development. The analytical method used is multiple linear regression with SPSS software. The results of this study indicate that health and education have a significant positive effect on the development of the province of West Sulawesi while the economic component does not affect the human development index.